PREDIKSI UMUR WADUK PANGLIMA JENDRAL BESAR SUDIRMAN BERDASAKAN HASIL PENGUKURAN ECHO-SOUNDING - Darmono, Darmono (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The echo sounding measurement is a method that can be used to know the change of dam volume directly on the field. This research aims to: (1) know the rest of the economic age of the Panglima Besar Jendral Sudirman (PBJS) Dam based on measurement and calculation the echo sounding data, and (2) give more detail view of the changes of the PBJS Dam condition viewed from sedimentation problem. The research activities were conducted in the PBJS Dam located on Kabupaten Banjarnegara, Jawa Tengah. The research utilized secondary data collected using documentation technique, consists of: (1) sediment volume/year, (2) dam effective volume, (3) dam volume, and total sediment volume year/ year. The data were the best mathematic curve interpretation supported by the Microsoft Excel software. The mathematic curve is indicated by the variance value coefficient (R) value from the various existing trend curve alternatives. The research results show that based on various mathematic curves being used, since 1999 the rest of operation age of the PBJS Dam lies between 17.37 to 20.71 years. This conclusion is a simple prediction without considering the future erosion control changes. The rest of the dam age assumps that the natural condition especially the sedimentation rate occuring in the dam does not change significantly compared to what happened on the previous years and it is not affected by the existing sand mining on the upstream of the dam. Keywords: dam age, echo sounding